(untitled) (Economics and region, 2024)
The article deals with the issues of effective management of logistics business processes as a key aspect of increasing the competitiveness and productivity of enterprises in modern conditions. The authors emphasize the importance of integrating various links of the logistics chain, the need to introduce the latest technologies and innovations to optimize logistics operations. Particular attention is paid to the analysis of the problems faced by enterprises: inefficient planning, inventory management, transportation delays and high logistics costs. The authors emphasize the need for an integrated approach to solving these problems, in particular through automation, improved warehouse management, transportation optimization, establishing partnerships with suppliers and customers, as well as staff training and development. The article contains practical recommendations for improving the efficiency of logistics management through the use of modern information technologies and innovative solutions. One crucial aspect often overlooked is the significance of sustainability in logistics operations. With growing environmental concerns and regulatory pressures, enterprises must prioritize eco-friendly practices throughout their supply chains. This entails reducing carbon emissions through optimized route planning, embracing alternative fuels and transportation modes, and promoting waste reduction and recycling initiatives. By aligning logistics strategies with sustainability goals, companies can not only mitigate environmental impact but also enhance brand reputation and attract eco-conscious consumers. In conclusion, addressing the multifaceted challenges of logistics business process management requires a holistic approach that integrates technological innovation, sustainability principles, and strategic collaboration. By embracing change, fostering a culture of continuous improvement, and leveraging data-driven insights, enterprises can navigate the complexities of modern logistics landscape and drive sustainable growth and competitive advantage in the global marketplace.